PERSEPSI MASYARAKAT TERHADAP KEBIJAKAN PEMERINTAH DAERAH ISTIMEWA YOGYAKARTA DALAM MEMBUKA TEMPAT PARIWISATA DENGAN MENERAPKAN PROTOKOL KESEHATAN YANG KETAT DI KONDISI PANDEMI COVID-19 - Budi, Surawan Setya; Indita Agustiyani, Alief; Dermawan, Arief (PRIMA EKONOMIKA, 2024)
The Government of the Special Region of Yogyakarta (DIY) adopted a policy of opening tourism spots in the Covid-19 pandemic situation with a strict health protocol, for the recovery of the economy of the city of the Special Region of Yogyakarta, which had fallen due to the presence of Covid-19. The opening of tourism places aims to increase the DIY economy so that it can recover quickly.This study aims to determine public perceptions of both tourism managers and domestic tourists with the opening of tourist attractions in the Covid-19 pandemic situation with strict health protocols, as well as knowing tourist attractions that are of interest during the Covid-19 pandemic. Respondents in this study amounted to 114 administrators of Rt, Rw, hamlet heads and village heads of Madurejo, Prambanan, Sleman, Yogyakarta. The data collection method used a questionnaire, a measuring instrument with a 5-point Likert scale was tested for validity and reliability and analyzed using descriptive analysis by finding the mean value of each statement item. The results of this study show that the community supports the DIY Government's decision to reopen tourist attractions in DIY. In terms of the health protocol required by the DIY government, the community supports the mandatory health protocol at tourist attractions in DIY, except for the health protocol regarding keeping a distance, the community has not accepted it well, because of the character of the Indonesian people who still like to gather in crowds. Open natural tourist spots with natural air circulation, wide open forests are the people's choice keywords: tourism, covid-19, economy, health